Research on naming and addressing technology of the Internet of things - Lingyun JIANG; Yanru MU; Hongbo ZHU (物联网学报, 2018)
With the rapid development of Internet of things,traditional naming and addressing schemes such as IP and URI are facing many challenges,including mobility,security and scalability,etc.In such context,the research progress of naming and addressing technology based on traditional network architecture and future network architecture was described.Then the development trend and core problems in this field were discussed.It was expected to be helpful for the domestic research in the related field.